Modelling intra-regional geographic mobility in a rural setting - Jan Ubøe; Inge Thorsen; David McArthur (European Regional Science Association (ERSA), 2011)
Large-scale models are often used in the urban planning context to model the effects of, for instance, a change in land-use policies or transportation infrastructure. This class of models accounts for factors such as the spatial distribution of jobs and workers, commuting flows, housing markets, modal choice and so on. One criticism of such models is their complexity, computational demands and data requirements. In this paper, we develop a model which shares certain features with large-scale models, but which is appropriate for studying development at the intra-regional level in a rural setting. The rural setting means that not all of the traditional features of a large-scale model are relevant, and these can therefore be omitted. This allows us to create a simple model which still captures the most relevant effects of large-scale models.
Keywords: 330